Usability Evaluation in Knowledge Management System (KMS) Using System Usability Scale (SUS) Method - Mahdiyah Afifah Sari; Ken Ditha Tania (The IJICS (International Journal of Informatics and Computer Science), 2022)
An unattractive system interface and the lack of user motivation in using the Knowledge Management System (KMS) is one of the reason why usability testing is needed. Usability testing aims to determine the usability of the system, whether the system is in accordance with the purpose of its application. Usability Testing will uses System Usability Scale (SUS) method which involves users in the test. The results of this study are usability scores and recommendations for improvement that have been developed using the prototyping method based on the results of problem identification. For the problem identification, researcher will uses interview technique with 5whys method. After all, the score results is 80.25 for prototype of system improvement. This research can be used as a reference in the development of the system later